2008
DOI: 10.1111/j.1442-2050.2008.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a disease-specific quality-of-life questionnaire in a large sample of Dutch achalasia patients

Abstract: The aim of this study was to validate a translated version of an achalasia-specific quality-of-life questionnaire (achalasia-DSQoL) by examining its psychometric properties in a Dutch cohort of achalasia patients. The achalasia-DSQoL was administered to 171 treated achalasia patients together with a clinical symptom score and the RAND-36. Validation methods included factor analysis, known-group techniques, Cronbach's alpha and Spearman rank correlation with other questionnaires and feasibility. About 72.5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…, 15 although the authors could not validate the measure in an independent series of patients because of the low prevalence of achalasia. Later on, this questionnaire has been validated in Dutch 16 . At the time the questionnaire by Urbach and colleagues was published we were developing our own questionnaire in Spanish language.…”
Section: Discusionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 15 although the authors could not validate the measure in an independent series of patients because of the low prevalence of achalasia. Later on, this questionnaire has been validated in Dutch 16 . At the time the questionnaire by Urbach and colleagues was published we were developing our own questionnaire in Spanish language.…”
Section: Discusionmentioning
confidence: 99%
“…To our knowledge, a disease‐specific HRQoL evaluation before and after therapy has not been ever performed in achalasia. After validating a Dutch version of Urbach’s questionnaire, Frankhuisen and coworkers 16 measured disease‐specific HRQoL in patients with achalasia after therapy, 21 but these patients had not been evaluated before treatment. They concluded that many patients with achalasia remain severely symptomatic after treatment and have decreased HRQoL.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing measures of HRQOL for GERD, dysphagia, achalasia, EoE, and Barrett’s esophagus were reviewed for content by three study investigators (TT, LK, and JP): Gastrointestinal Quality of Life Index (18), Quality of Life in Reflux and Dyspepsia Patients (19), GERD Analyzer (20), GERD Assessment Scales (21), Nepean Dyspepsia Index (22), MD Anderson Dysphagia Inventory (23), Laryngopharyngeal Reflux HRQOL scale (24), Reflux-QUAL (25), Eosinophilic Esophagitis QOL-A (7), Achalasia QOL (13), and the GERDQ (26). Relevant themes related to HRQOL were identified, and items from each questionnaire grouped by theme.…”
Section: Methodsmentioning
confidence: 99%
“…Disease-specific HRQOL measures exist for GERD (11,12), achalasia (13), eosinophilic esophagitis (7), dysphagia (14), and Barrett’s esophagus (15) but are not without limitation—one major concern is that the existing measures combine severity of disease with social/emotional impact, making it difficult to isolate the true impact of disease on HRQOL, as severe symptoms do not necessarily correlate with worsened quality of life (8,16). The second major concern about existing esophageal measures is that most of them are not transportable across clinical and research settings due to length, inefficiency of administration (e.g., having to give a different questionnaire to each presenting group), or they lack the complexity preferred by either the researcher or the clinician.…”
Section: Introductionmentioning
confidence: 99%